1989
DOI: 10.1080/00050068908259562
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the onset of agoraphobia

Abstract: Recent investigations have suggested that agoraphobiadevelops in response to stress. The present controlled study was undertaken in order to evaluate the assertion that psychosocial and/or physical stressors precede the development of agoraphobia with panic attacks. Data on life events, chronic stressors, and physiological distrubances were collected from 51 agoraphobics with panic attacks who had had the disorder for between 1 and 5 years.The life event data was then compared with matched controls drawn from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Nine studies, directly comparing PD patients and healthy controls, were identified reporting an increased overall number of LEs in a time period before the onset of PD. [15][16][17][18][19][20][21][22][23] Faravelli and co-workers observed an increased number of LEs in patients suffering from mental disorders, including anxiety disorders as compared to healthy controls [18] and an increase of LEs in PD patients 2-3 months before disorder onset. [16,17] An increase in the number of LEs by 100% has been reported to occur in the year before disorder onset, particularly with respect to six clusters that have been rated to be most distressing (e.g., threats to primary relationships, health, etc.).…”
Section: Life Events In Adulthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies, directly comparing PD patients and healthy controls, were identified reporting an increased overall number of LEs in a time period before the onset of PD. [15][16][17][18][19][20][21][22][23] Faravelli and co-workers observed an increased number of LEs in patients suffering from mental disorders, including anxiety disorders as compared to healthy controls [18] and an increase of LEs in PD patients 2-3 months before disorder onset. [16,17] An increase in the number of LEs by 100% has been reported to occur in the year before disorder onset, particularly with respect to six clusters that have been rated to be most distressing (e.g., threats to primary relationships, health, etc.).…”
Section: Life Events In Adulthoodmentioning
confidence: 99%
“…[16,17] An increase in the number of LEs by 100% has been reported to occur in the year before disorder onset, particularly with respect to six clusters that have been rated to be most distressing (e.g., threats to primary relationships, health, etc.). [19] Using path modeling techniques of an etiological PD model, Watanabe et al [23] discerned a direct effect of stressful LEs on the manifestation of PD. All studies reason that there is an increased risk of PD after experiencing stressful events and that LEs play a role as precipitating factors in the…”
Section: Life Events In Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of PAG is normally associated with stress. Numerous controlled studies have consistently found the frequency of life events experienced prior to onset to be significantly greater in PAG than in normal controls (Faravelli & Pallanti, 1989;Franklin & Andrews, 1989;Pollard et aL, 1989b). The experience of a major loss or separation in the year prior to onset has also been linked to the subsequent development of major depression (Roy-Byme et al, 1986).…”
Section: Risk Factors Associated With Onsetmentioning
confidence: 94%
“…It has been known for some time that panic patients experience great difficulty in understanding the cause of their panic (Franklin & Andrews, 1989;Goldstein & Chambless, 1978). Indeed one might say that the disorder would not arise if sufferers clearly understood the likely nature and causes of the psychosomatic changes they experience.…”
Section: Comprehensive Formulationmentioning
confidence: 99%